Bureaucratic Discretion in Implementation Village Fund Allocation Policy - Zacharias, Tehubijuluw; Amrin, Awaluddin; Yusriadi, Yusriadi; Rianti, Marlia (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2020)
This study aims to examine the practice of discretion carried out by bureaucrats in each stage of the implementation of the village budgetary budget policy in West Seram District. This research is focused on the act of discretion by frontline bureaucrats, namely village officials, including the village head, village secretary, and two employees in Piru Village and Eti Village in implementing the Village Fund Allocation policy. The interactive analysis model in this study began by examining all available data from various sources, namely the results of interviews, observations that have written in field notes, documents, and so on. After reading the study and study, the next step is to conduct data reduction, data presentation, and concluding. Based on the results of the study it is known that there are three forms of discretionary practices carried out by the authorities in relation to the implementation of the village fund budget in Piru Village and Eti Village, namely 1) restricting access to services, 2) technical changes in the allocation of microeconomic assistance and 3) technological changes in preparing reports.